A View at the Historical and Ancient Monuments of Kunduz Province-Afghanistan - Wafa, Amanuddin; Sarwari, Atiqullah; Habibi, Habib Rahman (RIRAI Publisher, 2024)
Kohandej is a combination of two words, alt and dej, meaning fence and old castle. Both words denote a high enclosure, and the historical course of Kunduz, which is the main basis of the enclosure at the time of the Aryan rulers of Balkh, namely Ki Khosro and Qiqbad, was formed in their time 1900 years before Christ. It was conquered and destroyed and rebuilt several times over time, earning it the name Kohandezh. The province of Kunduz, known as Kunduz, Kunduz,